Developing cultural quotient in the Malaysian English Language classroom: the role of Malaysian literatures in English - P. Shobha Menon,; Shanthini Pillai, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The incorporation of Malaysian Literatures in English into the Literature in English Component of the English Language curriculum has significantly diminished, resulting in its complete absence from Malaysian classrooms. An early examination of prior texts utilised in Malaysian classrooms indicated that the selection of materials inadequately represented Malaysia's multicultural society and the various ethnicities inside the nation. This advanced the fundamental purpose of the study: to determine how to select Malaysian Literatures in English that appropriately reflect Malaysia's complex societal fabric in schools, prioritising accurate representation and comprehensive inclusion. To achieve this, a custom-made checklist was devised to help lead a more socially cohesive process of text selection, especially in terms of ensuring that the texts selected represent and include all Malaysians as far as feasible. The second purpose of the study was to highlight the importance of having the correct book in the hands of young brains so as to establish a socially cohesive society that is sustainable. This paper selected a short story evaluated with a custom checklist to demonstrate how Culturally Quotient Modules can be utilised to teach Malaysian Literature in English in Malaysian classrooms in accordance with the newly implemented Common European Framework of Reference for English. The study concludes that reading Malaysian Literatures in English enhances language proficiency and fulfils a broader objective, specifically the fourth aspect of the Malaysian Education Blueprint 2013 - 2025, which is Unity, and the sixth attribute, which is National Identity. These two axioms can cultivate culturally intelligent Malaysians who welcome diversity.